Solution-processed resistive switching memory devices based on hybrid organic-inorganic materials and composites - Shan, Yingying (2020)
Resistive random-access memory (ReRAM) is expected to be the next-generation non-volatile memory device because of its fast operation speed and low power consumption. Switching media in most ReMAM are oxides which are rigid and require high-temperature processing. Here, we review two emerging types of low-cost solution-processed ReRAMs with sandwich structures: one is hybrid nanocomposites with charge-trapping nanoparticles (NPs) embedded in a polymer matrix, and the other is hybrid halide perovskites which have been intensively investigated recently for optoelectronic applications. We will review the recent developments in materials selection, device performance and operation mechanisms. Resistive switching in hybrid materials and composites is ubiquitous because of the abundant existence of charge-trapping defects and interfaces. The future challenges and potential breakthroughs will also be outlined.